2017
DOI: 10.1002/ajpa.23280
|View full text |Cite
|
Sign up to set email alerts
|

Neandertal talus bones from El Sidrón site (Asturias, Spain): A 3D geometric morphometrics analysis

Abstract: The Neandertal talocrural joint morphology is influenced by body size. The other Neandertal talus traits do not co-vary with it or not follow the same co-variation pattern as MH. Besides, the trochlear hypertrophy, the trochlear rims equality and the short neck could be inherited primitive features; the medial malleolar facet morphology could be an inherited primitive feature or a secondarily primitive trait; and the calcaneal posterior facet would be an autapomorphic feature of the Neandertal lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 69 publications
0
5
0
1
Order By: Relevance
“…Body size inferred by the lnCS is significantly correlated ( p < .001) with talar shape captured by PC1, but variation in talar shape is not solely due to the effects of size ( r = −0.38). Other authors who have studied talar morphological variation found that talar shape is significantly related to body size and this has been used to discern primitive traits from those influenced by body size (Parr et al, ; Rosas et al, ). However, there is not a generalized scaling rule in the talus of H. sapiens , and more broadly in hominoid primates, as a consequence of high intra‐specific variability that could be ultimately related to differences in sex, ontogenetic trajectories and likely activity level (Parr et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Body size inferred by the lnCS is significantly correlated ( p < .001) with talar shape captured by PC1, but variation in talar shape is not solely due to the effects of size ( r = −0.38). Other authors who have studied talar morphological variation found that talar shape is significantly related to body size and this has been used to discern primitive traits from those influenced by body size (Parr et al, ; Rosas et al, ). However, there is not a generalized scaling rule in the talus of H. sapiens , and more broadly in hominoid primates, as a consequence of high intra‐specific variability that could be ultimately related to differences in sex, ontogenetic trajectories and likely activity level (Parr et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism is an important factor underlying morphological variation in the entire human body, including the respiratory system (Frayer & Wolpoff, ; Franciscus, ; Krishtalka et al, ; Lam et al, ; Lockwood, ; Lockwood et al, ; LoMauro and Aliberti, ; McHenry, ; Molgan‐Seon et al, ; Plavcan, , , , ; Ponce de León et al, ; Rehg & Leigh, ; Reno et al, ; Reno et al, ; Richmond & Jungers, ; Wood, ; Bastir et al, ; Hall, ; Holton et al, ; Rosas & Bastir, , ; Rosas et al, ; Bastir et al, ; Carlson et al, ; Fischer & Mitteroecker, , ; İşcan & Shihai, ; Kranioti et al, ; García‐Martínez et al, ; Mitteroecker & Fischer, ; Rascón Pérez, ; Rosas et al, , ; Walker, ; Walker, ; Weinstein, ). García‐Martínez et al () quantified static thoracic morphology and found that males have more horizontally oriented ribs than females, as well as relatively shorter and wider ribcages, particularly in the caudal part.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism is a well‐documented source of morphological variation in recent and fossil hominins, and is observed in the entire human skeleton (Dominelli et al ; Frayer & Wolpoff, ; Franciscus, ; Krishtalka, Stucky, & Beard, ; Lam, Pearson, & Smith, ; Lockwood, ; Lockwood, Menter, Moggi‐Cecchi, & Keyser, ; McHenry, ; Plavcan, , , , ; Ponce de León et al, ; Rehg & Leigh, ; Reno, Meindl, McCollum, & Lovejoy, ; Reno, McCollum, Meindl, & Lovejoy, ; Richmond & Jungers, ; Wood, ). In modern humans, sexual dimorphism has been intensively studied in the skull (e.g., Bastir, Godoy, & Rosas, ; Hall, ; Holton, Yokley, Froehle, & Southard, ; Rosas & Bastir, , ; Rosas, Bastir, Martı́nez‐Maza, & de Castro, ), and in the postcranium (e.g., Bastir, Higuero, Ríos, & Garcia Martinez, ; Carlson, Grine, & Pearson, ; Fischer & Mitteroecker, , ; García‐Martínez, Torres‐Tamayo, Torres‐Sánchez, García‐Río, & Bastir, ; İşcan & Shihai, ; Kranioti, Bastir, Sánchez‐Meseguer, & Rosas, ; Mitteroecker & Fischer, ; Rascón Pérez, ; Rosas et al, , ; Weinstein, ). Skeletal morphological differences between sexes are usually accompanied by differences in size, so static allometry (Klingenberg & Zimmermann, ) is a factor to take into account when studying sex‐related differences in the human skeleton (Cheverud, ; Fischer & Mitteroecker, ; Freidline, Gunz, & Hublin, ; García‐Martínez et al, ; Humphrey, ; Rosas & Bastir, , ; Viðarsdóttir, O'Higgins, & Stringer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several morphological studies of the El Sidrón Neandertals have been conducted, including analyses of the crania (Rosas et al, 2008;Bastir et al, 2010;Pena-Melian et al, 2011), dentition (Rosas et al, 2006Dean et al, 2013), ribs (Bastir et al, 2015(Bastir et al, , 2017, clavicles (Rosas et al, 2016), humeri (Rosas et al, 2015) and tali (Rosas et al, 2017). Among the preserved Neandertal remains at El Sidrón are multiple hand bones, including carpals, metacarpals, and phalanges that were discovered between 1994 and 2009.…”
Section: Introductionmentioning
confidence: 99%